Legal education and profession in India / by P. L. Mehta and Sushma Gupta - Mehta, P. L. (New Delhi, 2000)
There is a growing need to modernize the Legal Education System in India. Thus, the authors have endeavoured to bring home a book on this subject. This book focuses attention on the origin and development of Legal Education System since pre vedic times with special emphasis on its subsequent up and down journey at different time periods of Indian history. Also it envelops and highlights the valuable material lying unnoticed in the texts of Legal Education Commissions, Committees, Statutes and Seminars in India. Finally, a detailed scrutiny of the Legal System of India has been conducted with a view to know that how far and to what extent our present legal education has contributed to the realization of the objectives of legal education. The study makes it clear that legal education in India is highly tilted in favour of theoretical knowledge of law rather than its functional aspect. The present work is thus an earnest attempt to throw light on different aspects of existing modes of imparting legal education in law faculties of Indian Universities which appear to have become unsuccessful in providing sufficient knowledge to the law students especially with regard to the functioning of the law courts and the skill which is needed to resolve the technicalities of law which generally surface during the course of their practice at the law courts.
Keywords: Law education